Behavior of the p-laplacian on thin domains - Silva, Ricardo P. [UNESP] (Hindawi, 2013)
We give the characterization of the limiting behavior of solutions of elliptic equations driven by the p -Laplacian operator with Neumann boundary conditions posed in a family of thin domains. © 2013 Ricardo P. Silva.